Lipid nanoparticle siRNA cocktails for the treatment of mantle cell lymphoma. Issue 2 (6th April 2018) - Knapp, Christopher M.; He, Jia; Lister, John; Whitehead, Kathryn A.
Abstract: Mantle cell lymphoma is an aggressive and incurable subtype of non‐Hodgkin B cell lymphoma. Patients typically present with advanced disease, and most patients succumb within a decade of diagnosis. There is a clear and urgent need for novel therapeutic approaches that will affect mantle cell lymphoma through a unique mechanism compared to current therapies. This study examined the use of RNA interference (RNAi) therapy to attack mantle cell lymphoma at the mRNA level, silencing genes associated with cancer cell proliferation. We identified a lipid nanoparticle formulated with the lipidoid 306O13 that delivered siRNA to JeKo‐1 and MAVER‐1 mantle cell lymphoma cell lines. Three therapeutic gene targets were examined for their effect on lymphoma growth. These included Cyclin D1, which is a cell cycle regulator, as well as Bcl‐2 and Mcl‐1, which prevent apoptosis. Gene knockdown with siRNA doses as low at 10 nM increased lymphoma cell apoptosis without carrier‐mediated toxicity. Silencing of Cyclin D1 induced apoptosis despite a twofold "compensation" upregulation of Cyclin D2. Upon simultaneous silencing of all three genes, nearly 75% of JeKo‐1 cells were apoptosing 3 days post‐transfection. Furthermore, cells proliferated at only 15% of their pretreatment rate. These data suggest that lipid nanoparticles‐formulated, multiplexed siRNA "cocktails" may serve as a beneficial addition to the treatment regimens for mantle cell lymphoma and other aggressive cancers. Abstract : Lipid nanoparticles loaded with siRNA were used to treat one of the most deadly subtypes of Non‐Hodgkin lymphoma, mantle cell lymphoma. Multiplexed gene silencing substantially inhibited cell growth and increased apoptosis rates to 75% of treated cells. These results underscore the potential benefit of incorporating RNAi therapy, which is mechanistically distinct from current therapies, into mantle cell lymphoma treatment regimens.